(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
This study aims to evaluate the effectiveness of interventions carried out by social work offices in educational institutions through the application of preventive, developmental, and therapeutic approaches, as well as to analyze their ability to improve students’ responses to problems within the educational environment. The study adopted a descriptive-analytical approach. The population consisted of social workers operating under the Educational Supervision Office in Souq Al-Juma’a, and the sample included 50 social workers. A questionnaire was used as the main data collection tool. The data were analyzed statistically using measures of central tendency and dispersion, correlation coefficients, Cronbach’s alpha reliability coefficient, frequencies, percentages, weighted means, and standard deviations. The findings revealed that preventive approaches contribute to a moderate extent in reducing behavioral problems and enhancing psychological and social stability. Developmental approaches were found to play a significant role in enhancing personal and social skills and capacities. Furthermore, therapeutic approaches were identified as the most effective in addressing behavioral, psychological, and academic problems, as well as in improving students’ adaptation and performance within educational institutions.